2004
DOI: 10.1038/sj.ijo.0802867
|View full text |Cite
|
Sign up to set email alerts
|

BMI, waist-circumference and waist-hip-ratio as diagnostic tests for fatness in adolescents

Abstract: OBJECTIVE:To evaluate the diagnostic accuracy of body mass index (BMI, kg/m 2 ), waist-circumference (WC) and waist-hipratio (WHR) as diagnostic tests for detecting fatness in adolescents. DESIGN: A cross-sectional analysis of 474 healthy adolescents aged 17 y was used. Measurements of height, weight, WC, hipcircumference and body fat percentage (%BF) were obtained. The diagnostic accuracy for detecting excess fatness was evaluated through receiver operating characteristics (ROC) analyses with %BF, measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
119
1
17

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 25 publications
13
119
1
17
Order By: Relevance
“…38 WC showed a slightly stronger association than BMI with the lipid and insulin risk factors, supporting the growing use of WC in preference to BMI 39,40 and consistent with the fact that WC is a measure of central obesity which is specifically related to the presence of CV risk factors. 41,42 Weight/hip ratio and weight/height ratios, as previously used in adults 43,44 albeit controversially in children, 15,21,45,46 were shown to be less strongly associated with the CV risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…38 WC showed a slightly stronger association than BMI with the lipid and insulin risk factors, supporting the growing use of WC in preference to BMI 39,40 and consistent with the fact that WC is a measure of central obesity which is specifically related to the presence of CV risk factors. 41,42 Weight/hip ratio and weight/height ratios, as previously used in adults 43,44 albeit controversially in children, 15,21,45,46 were shown to be less strongly associated with the CV risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated their diagnostic accuracy for adiposity, but as no accepted standard exists for classification of overweight and obesity based on body fat percentage (%BF), different cutoffs have been used (Reilly et al, 2000;Neovius et al, 2004Neovius et al, , 2005Zimmermann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of 5-to 18-year-old subjects they found that 25%BF for boys and 30%BF for girls, respectively, were suitable to define excess fatness. These cutoffs have been used in evaluations of BMI-based classification of overweight (Sardinha et al, 1999;Neovius et al, 2004Neovius et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The BMI is a proxy for body size (12) , whereas the WC measure reflects subcutaneous and visceral fat depots and can predict health risks in adults and children as young as 10 years of age (10) .…”
mentioning
confidence: 99%